Enterprise Interoperability VI Interoperability for Agility, Resilience and Plasticity of Collaborations - Mertins, Kai; Bénaben, Frédérick; Poler, Raúl; Bourrières, Jean-Paul (Springer eBooks, 2014)
A concise reference to the state of the art in systems interoperability, Enterprise Interoperability VI will be of great value to engineers and computer scientists working in manufacturing and other process industries and to software engineers and electronic and manufacturing engineers working in the academic environment. Over 40 papers, ranging from academic research through case studies to industrial and administrative experience of interoperability show how, in a scenario of globalised markets, where the capacity to cooperate with other firms efficiently starts to become essential in order to remain in the market in an economically, socially and environmentally cost-effective manner, the most innovative enterprises are beginning to redesign their business model to become interoperable. This goal of interoperability is essential, not only from the perspective of the individual enterprise but also in the new business structures that are now emerging, such as supply chains, virtual enterprises, interconnected organisations or extended enterprises, as well as in mergers and acquisitions. Establishing efficient and relevant collaborative situations requires to manage interoperability on a dynamic point of view: a relevant and efficient collaboration of organizations might require adaptation to remain in line with potentially changing objectives, potentially evolving resources, unexpected events, etc. Many of the papers contained in this, the seventh volume of Proceedings of the I-ESA Conferences have examples and illustrations calculated to deepen understanding and generate new ideas. The I-ESA'14 Conference from which this book is drawn was organized by Ecole Nationale Superieure des Mines d'Albi-Carmaux, on behalf the European Virtual Laboratory for Enterprise Interoperability (INTEROP-VLab) and sponsored by the International Federation for Information Processing (IFIP).